2006
DOI: 10.1158/0008-5472.can-05-3680
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of Primary Endothelial Cells by the K1 Protein of Kaposi's Sarcoma–Associated Herpesvirus

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is linked to three different human cancers: Kaposi's sarcoma, primary effusion lymphoma, and multicentric Castleman's disease. The Kaposi's sarcoma lesion expresses high levels of angiogenic factors and is comprised of a mixed cell population, including endothelial cells that are infected with KSHV. We find that the KSHV K1 protein is expressed in Kaposi's sarcoma lesions and can immortalize and extend the life span of primary human umbilical vein endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
151
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(162 citation statements)
references
References 50 publications
10
151
0
1
Order By: Relevance
“…[12][13][14][15][16] KSHV-infected PELs also display constitutive high-level activation of the PI3K/Akt/ mTOR pathway. 10 Our findings indicate that inhibiting this pathway is an effective modality for treating PEL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16] KSHV-infected PELs also display constitutive high-level activation of the PI3K/Akt/ mTOR pathway. 10 Our findings indicate that inhibiting this pathway is an effective modality for treating PEL.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have previously shown that individual viral proteins, such as KSHV K1, activate the PI3K/Akt pathway in B cells and endothelial cells. [12][13][14][15][16] Another viral protein, KSHV vGPCR, can also activate this pathway in endothelial and epithelial cells. [17][18][19][20][21] KSHV-infected PELs display constitutive activation of the PI3K/ Akt/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Chief among these is ORF-K1, a transmembrane signaling molecule whose activity mimics signaling via the B cell antigen receptor (159). These findings may be important in KS pathogenesis, since it has been shown that K1 overexpression in primary endothelial cells can substantially extend their lifespan (160).…”
Section: How Does Kshv Infection Predispose To Ks?mentioning
confidence: 99%
“…KS lesions express all 3 factors, and lytic infection is associated with strong upregulation of angiopoietin 2 (174,175). And v-GPCR is not the only gene expressed in lytic infection that can upregulate VEGF; ORF-K1 expression, which is strongly upregulated during lytic infection (66,176), also has this activity (177,178). Other lytic viral proteins can upregulate inflammatory signaling by the host.…”
Section: How Does Kshv Infection Predispose To Ks?mentioning
confidence: 99%
“…[14][15][16] Others have shown that K1 immortalizes cells. 11 To determine whether K1 regulates apoptosis, we focused on the Fas (Apo-1/ CD95) pathway, the most important apoptosis pathway that determines the fate of lymphocytes. 17,18 To delineate the role of K1 in cell survival, in our present study we tested the ability of this protein to interfere with apoptosis in K1-transfected mice and in BJAB lymphoma cells and hematopoietic and endothelium-related cell lines (THP-1 macrophages/monocytes, U937 monocytes, and KS SLK cells) expressing K1 or a K1 mutant with an ITAM (K1m) with the Fas ligand, an anti-Fas antibody, and other agents that induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%